Analysis of the physical fitness of civil aviation pilots based on heart rate variability research - Semenova, G.I.; Erkomayshvili, I.V.; Solomyannyy, A.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to analyse the physical condition of civil aviation pilots and develop an optimal physical training programme aimed at improving flight safety. Methods and structure of the study. The analysis of the most informative indicators of heart rate variability was carried out to assess the functional state of pilots, including time domain metrics such as: SDNN – Standard Deviation of NN intervals (average value of variability in milliseconds and reflecting heart rate variability over a certain time), RMSSD – Root Mean Square of Successive Differences (metric showing activity of the parasympathetic nervous system and reflecting changes in the duration of intervals between heartbeats), frequency domain: LF/HF – Low Frequency/High Frequency and specific Russian indices: Bayevsky index (stress index of regulatory systems), IARS (indicator of adaptation of regulatory systems). Results and conclusions. The scientific work was carried out using the Varicard 3.0 system. 42 active civil aviation pilots of the Russian Federation aged 25 to 40 years participated in it, randomly assigned to experimental (n=21) and control (n=21) groups. The experimental group used a developed physical training program lasting 2 months, after which a significant improvement in heart rate variability was revealed. The control group showed no significant changes in the same indicators. As a result of the research, a universal method for identifying the physical condition of pilots and a structured training program for improving physical condition in order to increase flight safety were developed.